Time immemorial: The landscape archaeology of Dickett’s Field, Hampshire ‘Why be high? 500000 years occupation on Dickett’s Field Hampshire - William, S; Professor William Scott-Jackson (2004)
Spatial analysis combines the capabilities of database systems with the presentation of computer mapping, to model the spatial relationships between archaeological entities and topography, such as defining catchment areas and the views from and to monuments. To date, such applications have generally taken a functional approach, treating spatial relationships, and space itself, as depersonalised and neutral. Here, spatial analysis is used to determine the cognitive locational criteria of people of three distinct periods, Lower/Middle Palaeolithic (lithic scatters), later prehistoric (banked enclosure) and Roman (road) on the Dickett’s Field high-level plateau. The advantages and disadvantages of alternative hypothetical locations were modelled and compared to the chosen locations, as indicated by the archaeological evidence. The results of this research demonstrate that spatial analysis can be used to model hypothetical locations and to identify the decision making criteria of past peoples.